Multiple-Clones of Streptococcus agalactiae harbouring lnuB gene - Faccone, Diego (2010)
Fil: Faccone, Diego. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Servicio de Antimicrobianos; Argentina.